2013
DOI: 10.1111/all.12155
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐mediated anaphylaxis and allergic reactions to idursulfase in patients withHunter syndrome

Abstract: Anaphylaxis related to infusion of idursulfase is mediated by anti-idursulfase IgE antibody, which might be produced by de novo synthesis. SPT is useful in predicting the occurrence of anti-idursulfase IgE-mediated anaphylaxis during infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
0
18
0
8
Order By: Relevance
“…However, life-threatening anaphylactic reactions can occur in patients receiving ERT. In a previous study (29), anaphylaxis associated with the infusion of idursulfase was mediated by anti-idursulfase IgE antibodies, which can be produced by de novo synthesis. The skin-prick test was useful at predicting the occurrence of antiidursulfase IgE-mediated anaphylaxis during infusion.…”
Section: Ert In South Koreamentioning
confidence: 94%
“…However, life-threatening anaphylactic reactions can occur in patients receiving ERT. In a previous study (29), anaphylaxis associated with the infusion of idursulfase was mediated by anti-idursulfase IgE antibodies, which can be produced by de novo synthesis. The skin-prick test was useful at predicting the occurrence of antiidursulfase IgE-mediated anaphylaxis during infusion.…”
Section: Ert In South Koreamentioning
confidence: 94%
“…For some patients, however, immune responses to ERT have resulted in adverse reactions, including mild to life-threatening hypersensitivity responses [10,11,12].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T with IgE mAb) [35]. Although infusion reactions can be challenging to manage in some patients, they…”
mentioning
confidence: 99%
“…21 No IgE antibodies were detected in any of the studies described above. 14,[19][20][21] Recently, Kim et al 38 identified specific …”
Section: Antibodiesmentioning
confidence: 99%
“…The authors concluded that this immediate-type hypersensitivity is mediated by antiidursulfase IgE antibodies, which might be produced by the de novo synthesis. 38 The results of a post hoc analysis of data from the Phase II/III study and extension study were presented by Barbier et al, 39 in order to evaluate the association between anti-idursulfase antibody status and the efficacy and safety of idursulfase, administered at the dose of 0.5 mg/kg weekly for 105 weeks, in an attenuated, treatment-naïve population of patients aged 5 years and older. Thirty-two out of the 63 patients analyzed (51%) developed at least a single sample that was positive for anti-idursulfase antibodies without a decrease in 6MWT distance, a decrease in %FVC response, or an increase in liver and/or spleen volume.…”
mentioning
confidence: 99%